Cultivated olive - wild olive - Havemann, J. C. T. (1997)
The Olive tree metaphor surfaces within the content of the relationship between the Jews and Gentiles in Romans 9-11. The grafting in of a wild olive branch into a tame olive is against all sound botanical practice. By using a specific theory on metaphor it becomes possible to come to grips with the exegesis and hermeneutics of this challenging rhetorical device. It also opens up text gappings which the ordinary reader can actualise as God's promises are open to all people.
Keywords: Wild olive; Olive tree metaphor; Hebrew Bible; Cultivated olive; Book of Romans